Roles of Multiple Globus Pallidus Territories of Monkeys and Humans in Motivation, Cognition and Action: An Anatomical, Physiological and Pathophysiological Review - Saga, Yosuke; Hoshi, Eiji; Tremblay, Léon (Frontiers in Neuroanatomy, 2017)
The globus pallidus (GP) communicates with widespread cortical areas that support various functions, including motivation, cognition, and action. Anatomical tract-tracing studies revealed that the anteroventral GP communicates with the medial prefrontal and orbitofrontal cortices, which are involved in motivational control; the anterodorsal GP communicates with the lateral prefrontal cortex, which is involved in cognitive control; and the posterior GP communicates with the frontal motor cortex, which is involved in action control. This organization suggests that distinct subdivisions within the GP play specific roles. Neurophysiological studies examining GP neurons in monkeys during behavior revealed that the types of information coding performed within these subdivisions differ greatly. The anteroventral GP is characterized by activities related to motivation, such as reward seeking and aversive avoidance; the anterodorsal GP is characterized by activity that reflects cognition, such as goal decision and action selection; and the posterior GP is characterized by activity associated with action preparation and execution. Pathophysiological studies have shown that GABA-related substances or GP lesions result in abnormal activity in the GP, which causes site-specific behavioral and motor symptoms. The present review discusses the anatomical organization, physiology and pathophysiology of the three major GP territories in nonhuman primates and humans.